The eye, a spy hole on human mind: Spontaneous blink rate and amplitude, and their variability, as new psychobiological markers of anxiety - Alon Tomashin; Francesca Fusina; Marco Marino; Alessandro Angrilli (PLoS ONE, 2025)
Spontaneous blink is a behavioral index that proved to represent an interesting window on the human brain and mind. It can be easily extracted from the electroencephalogram, eye-tracking or video-recording. In past studies Blink Rate (BR) was found to be modulated by attention, emotion, and fatigue. We added to current research by testing some new blink-related measures (Blink Amplitude-BA, Blink Rate Variability-BRV and Blink Amplitude Variability-BAV) that could represent valid biomarkers of state and trait anxiety. We measured blinking at rest using the vertical electrooculogram extracted from the EEG recordings collected from 50 healthy female students and correlated it with their State and Trait Anxiety scores. We also correlated anxiety with the individual blinking measured during an emotional film viewing session. During resting state a good correlation among the four blink measures was found but, concerning individual differences, a significant correlation emerged only between BA and State Anxiety (R 48 = 0.288). This result is strikingly similar to that found in our past study between startle reflex amplitude and State Anxiety, and suggests that BA might represents a more ecological and easier correlate of anxiety than startle. During film viewing the correlation among blink measures was greater with respect to resting state. In addition, correlation between BA and State Anxiety was greater (R 44 = 0.557), but also BR and BRV indexes were significantly correlated with State Anxiety (R 44 = 0.418 and R 44 = −0.357 respectively). Interestingly, during clip vision the correlation between BA and Trait Anxiety became significant (R 44 = 0.354) but this effect was mediated by State Anxiety. Our results reveal how these blinking indexes are promising markers of anxiety. In particular, BA was the most effective biomarker of State Anxiety, but under specific conditions, also of Trait Anxiety. This fosters the use of blink measures in minimally invasive paradigms and experiments with ecological setting.